2012
DOI: 10.1016/j.jdent.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Protection of sound enamel and artificial enamel lesions against demineralisation: Caries infiltrant versus adhesive

Abstract: OBJECTIVE: To compare the protective potential of a conventional adhesive, a caries infiltrant and a combination of both against acidic challenge in vitro. METHODS: One-hundred-and-fifty discs from bovine lower central incisors were fabricated. Seventy-five samples remained untreated, whereas the other half was subjected to a demineralisation process (14 days, acidic buffer, and pH 5) to create artificial enamel lesions. Specimens were then radioactively irradiated, and each 15 sound and demineralised specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 26 publications
2
43
0
3
Order By: Relevance
“…5,11 Recently, a low-viscosity caries infiltrant with high penetration ability has been shown to increase the protective capacity of conventional adhesives against demineralization. 12 This new resin has been originally developed to arrest WSL progression and to prevent further demineralization by forming a resistant condensed layer via infiltrating the demineralized enamel. 13 In contrast to conventional sealants, where the physical barrier remains on the enamel surface as a covering coat, this infiltrant presents rapid capillary penetration into the pores creating a diffusion barrier within the enamel with very low-viscosity and superior surface wetting abilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,11 Recently, a low-viscosity caries infiltrant with high penetration ability has been shown to increase the protective capacity of conventional adhesives against demineralization. 12 This new resin has been originally developed to arrest WSL progression and to prevent further demineralization by forming a resistant condensed layer via infiltrating the demineralized enamel. 13 In contrast to conventional sealants, where the physical barrier remains on the enamel surface as a covering coat, this infiltrant presents rapid capillary penetration into the pores creating a diffusion barrier within the enamel with very low-viscosity and superior surface wetting abilities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, new retention areas for plaque accumulation at the sealed margins are being avoided. 12,13 However, in spite of the deeper penetration of carious lesions where there is a porous structure for the resin to infiltrate, it has not been shown if this resin can infiltrate phosphoric acid etched sound enamel where only limited capillary diffusion is imaginable.…”
Section: Introductionmentioning
confidence: 99%
“…17 The use of adhesives to reduce enamel dissolution after carious acid challenge has also been tested. 18 The adhesives tested in our study were chosen because they are self-etching and do not require prior application of a strong acid for getting retention, which would result in an additional wear on the already eroded surface, thus being more aggressive. Hermsen and Vrijhoef 33 showed that application of 37% phosphoric acid for 15 seconds on the enamel surface promotes removal of about 4.9 μm.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Another study has applied the adhesive over the enamel, and its results showed decreased dissolution of enamel after acid challenge. 18 The treatment of cavity walls with Nd:YAG laser has been investigated to improve the bond strength. However, it was shown that it reduces the bond strength to enamel and dentin.…”
Section: 14mentioning
confidence: 99%
“…Recently, approaches have been made to extend this preventive concept to smooth enamel surfaces [31,32]. The superficial penetration and surface coating of the adhesive and/or caries infiltrant is considered as a treatment option for protecting enamel dissolution [33].…”
Section: Dental Coating Materials In the Futurementioning
confidence: 99%